Control and Physiological Determinants of Sympathetically Mediated Brown Adipose Tissue Thermogenesis - Richard, Denis; Monge Roffarello, Boris; Chechi, Kanta; Labbé, Sébastien M.; Turcotte, Éric (Frontiers in Endocrinology, 2012)
Brown adipose tissue (BAT) represents a remarkable heat-producing tissue. The thermogenic potential of BAT is conferred by uncoupling protein 1, a protein found uniquely in brown adipocytes. BAT activity and capacity is controlled by the sympathetic nervous system (SNS), which densely innervates brown fat depots. SNS-mediated BAT thermogenesis is essentially governed by hypothalamic and brainstem neurons. BAT activity is also modulated by brain energy balance pathways including the very significant brain melanocortin system, suggesting a genuine involvement of SNS-mediated BAT thermogenesis in energy homeostasis. The use of positron emission tomography/computed tomography scanning has revealed the presence of well-defined BAT depots in the cervical, clavicular, and paraspinal areas in adult humans. The prevalence of these depots is higher in subjects exposed to low temperature and is also higher in women compared to men. Moreover, the prevalence of BAT decreases with age and body fat mass, suggesting that BAT could be involved in energy balance regulation and obesity in humans. This short review summarizes recent progress made in our understanding of the control of SNS-mediated BAT thermogenesis and of the determinants of BAT prevalence or detection in humans.